Meticillin-resistant Staphylococcus aureus transmission among healthcare workers, patients and the environment in a large acute hospital under non-outbreak conditions investigated using whole-genome sequencing. (December 2021) - Kinnevey, P.M.; Kearney, A.; Shore, A.C.; Earls, M.R.; Brennan, G.; Poovelikunnel, T.T.; Humphreys, H.; Coleman, D.C.
Summary: Background: The role of meticillin-resistant Staphylococcus aureus (MRSA) colonization of healthcare workers (HCWs), patients and the hospital environment in MRSA transmission in non-outbreak settings is poorly understood. Aims: To investigate transmission events (TEs) involving HCWs, patients and the environment under non-outbreak conditions in a hospital with a history of endemic MRSA using whole-genome sequencing (WGS). Methods: HCW ( N = 326) and patient ( N = 388) volunteers on nine wards were tested for nasal and oral MRSA colonization over two years. Near-patient environment ( N = 1164), high-frequency touch sites ( N = 810) and air ( N = 445) samples were screened for MRSA. Representative MRSA and clinical isolates were analysed by WGS and core-genome multi-locus sequence typing (cgMLST). Closely related isolates (≤24 allelic differences) were segregated into related isolated groups (RIGs). Findings: In total, 155 MRSA were recovered: clinical isolates ( N = 41), HCWs ( N = 22), patients ( N = 37), environmental isolates ( N = 55). Nine clonal complexes (CCs) were identified among 110/155 MRSA sequenced with 77/110 assigned to CC22. Seventy-nine MRSA segregated into 17 RIGs. Numerous potential TEs were associated with CC22-MRSA (RIGs 1–15), CC45-MRSA (RIG-16) and CC8-MRSA (RIG-17). RIG-1, (the largest RIG) contained 24 ST22-MRSA-IVh from six HCWs, six patients, four clinical and eight environmental samples recovered over 17 months involving 7/9 wards. TEs involving HCW-to-patient, HCW-to-HCW, patient-to-patient and environmental contamination by HCW/patient isolates were evident. HCW, patient, clinical and environmental isolates were identified in four, nine, seven and 13 RIGs, respectively, with 12/13 of these containing isolates closely related to HCW and/or patient isolates. Conclusions: WGS detected numerous potential hospital MRSA TEs involving HCWs, patients and the environment under non-outbreak conditions.